(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study examines the ’dual burden’ of malnutrition—coexisting undernutrition (micronutrient deficits) and overnutrition (obesity)—among corporate professionals (aged 30–40 years) in India’s Mumbai Metropolitan Region (MMR) and quantifies its impact on workplace performance. Despite Mumbai’s affluence, the workforce exhibits a nutritional paradox, evidenced by high rates of obesity (over 59% of employees) and severe micronutrient deficiencies (e.g., 54.4% female anemia, 94.9% low riboflavin intake).1 Using mixed-method data analysis (n=214), empirical correlations were established: anemic workers show a 32% higher absenteeism rate, while daily fruit consumption correlates with an 18% higher composite performance score.1 The findings attribute this crisis primarily to structural barriers—namely, demanding schedules, high stress, and reliance on convenience foods—which constrain healthy dietary choices.1 The research concludes that strategic, theory-driven interventions focused on environmental modification (e.g., mandatory healthy canteen standards and subsidies) are necessary to enhance workforce resilience, secure human capital, and realize high organizational returns on investment.2